The Factor-Proportions Model With Many Nations, Goods and Factors: Theory and Evidence - Harkness, Jon (The Review of Economics and Statistics, 1983)
RECENTLY, several authors have markedly improved our understanding of the factorproportions trade model when there are arbitrarily many goods, factors and/or nations. Vanek (1968) appears to be the first rigorously to derive theorems, in the spirit of the simple Heckscher-Ohlin (H-O) theory, concerning the factor content of a nation's total trade. Subsequently, Horiba (1974) has investigated conditions under which Vanek's results hold bilaterally for trade among many nations. Lastly, in Harkness (1978), I considered the implications of Vanek's model for a nation's total, but not its bilateral, commodity trade. Nonetheless, none of these models nor their implications have been subjected to rigorous empirical tests.' This paper provides such tests on observed trade patterns among Canada, the United States and the Rest-of-the-World (ROW). Section I briefly reviews the Vanek-Horiba version of the factor-proportions model, demonstrating how a nation's total and bilateral net factor-service trade flows are linked to her total and bilateral relative factor endowments. The implications for direct commodity trade are derived in section II by extension of my earlier (1978) results. Section III deals with problems arising from the absence of some data necessary to empirical implementation of the model. Section IV presents the results of empirical tests. Conclusions are found in section V.